Seroprevalencia e incidencia de Brucella sp en vacunadores del Programa para el control de brucelosis bovina, en el Departamento de Antioquia-Colombia (2010)
ABSTRACT: Brucellosis is a public health problem in the occupational context of abattoir workers and cattle vaccinators. The exploration of positives and its associated factors is necessary to the establishment of preventive measures on this population. The objective of the present study was to determine the seroprevalence and incidence of Brucellosis in workers of the Brucellosis control program in Antioquia – Colombia. It took place a cohort study in two different moments, before the cycle and after the cycle. For the first moment there were 251 individuals and for the second 221. Every individual was explored by a complete questionnaire. In the other hand all workers were subject to vennopunction and blood extraction, for serology examination with Rose Bengal test and Competitive ELISA. They were examinated sociodemographic, occupational and clinical variables in all the participants of the study. The seroprevalence of Rose Bengal test (RBT) for the first moment of the study was 10.8 (IC 95% 6.39- 14.32) in the second moment the seroprevalence was 15.4% (IC 95% 10.40 -20.36) with the same test. The seroconvertion was 5.7% (IC 95% 2.002-9.493) para RBT. There were no significant differences between the positivity proportions in both moments of the study, therefore at the individual level seroconvertion it’s suggesting that these individuals are at occupational risk and this will result, with a longer surveillance period among this group in significative results.